Strategic market management - Aaker, David A. (New Jersey : Wiley, 2014)
"Marketing professionals need to be able to adapt new strategies in order to keep their companies relevant. Aaker walks them through the strategic challenges created by the dynamic nature of today's markets. Strategic Market Management, 10th Edition emphasizes a customer perspective and the fact that every strategy should have a value proposition that is meaningful to the customers. Sections are included on energizing the business and how to overcome the barriers that powerful organization silos create to inhibit cooperation and communication. Specific case studies delve into real world and engaging issues"--
Includes index.
Keywords: Marketing -- Management; Strategic planning; BUSINESS & ECONOMICS / Marketing / General